Life Cycle Assessment Proses Produksi Pulp dari Kayu Akasia (Studi Kasus: PT Tanjungenim Lestari) - Nur Indrianti; Nyayu Ferliana Widya Ningsih; Partoyo Partoyo (Seminar Nasional Teknik Kimia Kejuangan, 2017)
The increasing global demand for paperand the opportunity for Indonesia to become one of the the top three players in the world pulp and paper industry tend to increase the capacity of national pulp production in the coming years.On the other hand the production process of pulp gives rise to the environment impacts such as increasing use of energy and environmental pollution. This study aims to do the environmental assessment of pulp production using Life Cycle Assessment by means of Simapro Software Version 8.0.3.14.As the object of the study we took a pulp production process using acacia wood as raw material that is undertaken by a pulp producer named PT Tanjungenim Lestari. The company is located in Muara Enim, South Sumatera, Indonesia. The results of the study show that the highest environmental impacts generated from the pulp production process include marine aquatic depletion and human toxicity resulted from chip preparation, digesting,and washing/screening processes.